PENERAPAN MODEL PEMBELAJARAN STAD DENGAN MEDIA TEKA-TEKI SILANG DAN MODEL PEMBELAJARAN DISCOVERY LEARNING KONSEP SISTEM GERAK PADA MANUSIA UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS VIII SMP NEGERI 1 AMBON - Yuliana A Maselkosu; Dominggus Rumahlatu; S I. A. Salmanu (Program Studi Pendidikan Biologi FKIP Unpatti, 2018)
Background: The STAD model is to motivate students to support each other and help one another in mastering the abilities taught by the teacher. Crosswords are a game of sharpening the brain where we have to fill in the blank spaces (in the form of white boxes) with the letters that form a word based on the instructions given. Method: Design of experimental research with the type of research used is descriptive comparative. The research subjects were the eighth grade students of Ambon 1 Junior High School, totaling 26 students. The instruments used were initial test and final test questions, observation sheets, student worksheets and group worksheets. Results: Research shows that the application of the STAD Cooperative type learning model with Cross Puzzle media can improve student learning outcomes. On average all aspects of value have increased. Can be seen in the achievement of the estimated student score of 83.46%. Continued hypothesis testing using the t-test with the value of thit> ttab (2.27> 2.01) thus there are differences in the improvement of student learning outcomes using the STAD type cooperative learning model with a crossword puzzle media. Conclusion: There are differences in the application of the STAD learning model with crossword media and discovery learning learning models of motion systems concepts in humans to improve learning outcomes of class VIII students of SMPN 1 Ambon, it is evident that the results of t-test analysis where t count> t table that the STAD model with media crossword puzzles is more effective for improving student learning outcomes than the Discovery Learning model